Analysis of the Impact of Subsidized Housing Development on the Life Satisfaction of Surrounding Communities in Alam Barajo District Jambi City - Shintiya, Shintiya; Suandi, Suandi; Syarifuddin, Hutwan (Rifa'Institute, 2026)
Introduction: The development of subsidized housing in urban areas aims to meet the housing needs of low-income communities. However, large-scale housing development can also cause changes in the environmental, social, and economic conditions of surrounding communities that potentially influence community life satisfaction. Objective: This study aims to analyze the influence of subsidized housing development on community life satisfaction in Alam Barajo District, Jambi City through environmental, social, and economic aspects. Method: This study uses a quantitative approach with a survey method involving 100 respondents who live around subsidized housing areas. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. Results and Discussion: The results of the study show that subsidized housing development has a significant influence on the environmental, social, and economic aspects of the community. However, in relation to community life satisfaction, only the social variable has a significant influence. The indirect effect analysis also shows that the social aspect acts as a mediator in the relationship between subsidized housing development and community life satisfaction. Conclusion: Subsidized housing development has an impact on the environmental, social, and economic conditions of the community in Alam Barajo District. However, community life satisfaction is more influenced by the social dynamics formed within the residential environment